2005
DOI: 10.1097/01.bot.0000164592.96724.a9
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Plasma Chemical Treatment of Titanium Schanz Screws Reduces Pin Loosening

Abstract: Objective: This study was designed to assess the benefits of a new Anodic Plasma Chemical calcium-phosphate (APC-CaP) surface treatment on reducing pin track infection and pin loosening in comparison to anodized titanium (Ti) during external fracture fixation.Methods: A tibial midshaft, transverse, 6-mm gap osteotomy was created in 17 adult female Swiss alpine sheep. The tibia was stabilized with an external fixator and 4 Schanz screws of Ti or APC-CaP-treated Ti. The sheep were examined during a 12-week obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…There is a clear trend that the irregular microrough APC‐coated surfaces initially induced good bone forming activity observed until week 6, after which point, activity was similar to that of the HA‐coated samples. Our results are in line with another previous study33 investigating the benefit of APC treatment of titanium Schanz screws. This study was carried out as a result of the good biocompatibility shown by this initial study of APC‐treated screws.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There is a clear trend that the irregular microrough APC‐coated surfaces initially induced good bone forming activity observed until week 6, after which point, activity was similar to that of the HA‐coated samples. Our results are in line with another previous study33 investigating the benefit of APC treatment of titanium Schanz screws. This study was carried out as a result of the good biocompatibility shown by this initial study of APC‐treated screws.…”
Section: Discussionsupporting
confidence: 93%
“…The extraction torque for APC‐CaP pins was higher than for cpTi pins, which is in agreement with our results. The authors conclude that the APC‐CaP surface improves the clinical performance of Ti pins with respect to pin loosening and pin track infection,33 which added to the original data from our study, highlighting the promise for APC‐coated cpTi screws for biomedical applications. Previous studies in our laboratory34 have also shown the excellent cytocompatibility in vitro of APC‐CaP‐treated surfaces in terms of osteoblast and fibroblast attachment (VPS not tested).…”
Section: Discussionsupporting
confidence: 67%
“…The ethanol may not have penetrated the tissue causing some deterioration of the tissue resulting in unclear histology slides (Table III). It is difficult to compare our histological results to the literature since previous animal studies examining pin tract infection appear to have only used clinical signs,46–49 positive cultures,56 or both clinical signs and positive cultures57 to determine the presence of pin tract infection in animal studies. However, the potential presence of false negatives in the histological results did not appear to greatly affect the overall infection conclusion for each rabbit since cultures and/or histology results confirmed infection in 18 of 20 rabbits displaying clinical signs of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The rabbit was classified as infected when at least two of the three infection criteria were present: (1) greater than Grade I clinical signs of infection, (2) positive culture for one or more of the tissue samples, and/or (3) positive histology indicative of infection for one or more of the tissue samples. Although most human and animal studies investigating pin tract infection base infection on clinical signs alone,46–54 this study required conformation through culture or histology to minimize false positive results due to clinical signs of infection being caused by the rabbit irritating the pin site (i.e., licking/chewing).…”
Section: Methodsmentioning
confidence: 99%
“…Thicker oxide coatings and incorporation of Ca-P ions enhances biocompatibility properties (45). In fact, the incorporation of Ca-P into the layer has been shown to increase the adhesion to titanium, compared to plasma sprayed HA coatings using ISO test 13779-2 (58). In addition to the bone promoting Ca-P ions, roughness is also increased on the anodized titanium, which is known to increase bone formation.…”
Section: Nanostructural Microstructural Chemical and Mechanical Promentioning
confidence: 99%